2019
DOI: 10.1016/j.jmoldx.2018.10.005
|View full text |Cite
|
Sign up to set email alerts
|

t(3;8)(q26.2;q24) Often Leads to MECOM/MYC Rearrangement and Is Commonly Associated with Therapy-Related Myeloid Neoplasms and/or Disease Progression

Abstract: t(3;8)(q26.2;q24) is a rare recurrent cytogenetic abnormality that is associated with myeloid neoplasms. Of 20 patients with t(3;8)(q26.2,q24), 8 had therapy-related acute myeloid leukemia (AML), 3 therapy-related myelodysplastic syndrome, 4 blast phase of chronic myeloid leukemia, 1 relapsed AML, 1 AML transformed from chronic myelomonocytic leukemia, 1 blast phase of an unclassifiable myeloproliferative neoplasm, 1 de novo myelodysplastic syndrome, and 1 de novo AML. Nineteen patients presented with cytopeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Unlike lymphoid malignancies, where MYC overexpression is mostly associated with its translocation, the cause of MYC aberrant expression and activity in myeloid malignancies is not thoroughly established [ 29 , 608 ]. However, a rare recurrent translocation t(3;8) (q26.2;q24), causing MECOM-MYC rearrangement, has been reported to be associated with therapy-related and relapsed AML as well as AML transformed from Ph + CML [ 609 , 610 ]. Recently, in a detailed and comprehensive study, hotspot mutations in the MYC gene have been identified in AML patients [ 611 ].…”
Section: The Role Of Myc In Hematopoiesis and Hematological Malignanciesmentioning
confidence: 99%
“…Unlike lymphoid malignancies, where MYC overexpression is mostly associated with its translocation, the cause of MYC aberrant expression and activity in myeloid malignancies is not thoroughly established [ 29 , 608 ]. However, a rare recurrent translocation t(3;8) (q26.2;q24), causing MECOM-MYC rearrangement, has been reported to be associated with therapy-related and relapsed AML as well as AML transformed from Ph + CML [ 609 , 610 ]. Recently, in a detailed and comprehensive study, hotspot mutations in the MYC gene have been identified in AML patients [ 611 ].…”
Section: The Role Of Myc In Hematopoiesis and Hematological Malignanciesmentioning
confidence: 99%
“…AML is a heterogeneous disease, with EVI1 positive (EVI1+) inv(3)/t(3;3) patients being identified as a subgroup with a very poor response to therapy [16][17][18][19] . Besides inv(3)/t(3;3), many other EVI1 + AML cases with 3q26 rearrangements have been reported, including translocations t(2;3)(p21;q26), t(3;7)(q26;q24), t(3;6)(q26;q11), and t(3;8)(q26;q24) 18,[20][21][22][23][24][25][26][27] . We hypothesize that in all these rearrangements EVI1 overexpression is induced by the repositioning of an enhancer that can interact with the EVI1 promoter, as shown for inv(3)/t(3;3) AML 14,15 .…”
mentioning
confidence: 99%
“…We hypothesize that in all these rearrangements EVI1 overexpression is induced by the repositioning of an enhancer that can interact with the EVI1 promoter, as shown for inv(3)/t(3;3) AML 14,15 . We performed targeted next-generation sequencing (NGS) of the long arm of chromosome 3 (3q-seq) in translocation t(3;8)(q26;q24) AML harboring an EVI1/MYC rearrangement 22,27 . Applying CRISPR-Cas9 technology, we generated a human t(3;8) cell line model with an eGFP reporter cloned 3' of EVI1.…”
mentioning
confidence: 99%
“…Conventional G-banded chromosomal analysis (karyotyping) has been routinely performed on unstimulated 24-h and 48-h BM aspirate cultures using standard techniques as we have reported previously [6] , [7] , [8] . Interphase-, metaphase-, map-back FISH and WCP have been performed by following existing laboratory protocols as reported previously [6] , [7] , [8] , [9] . The following probe/probe set have been employed for this study.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%